2020
DOI: 10.1088/1748-9326/ab6999
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the 2018 heatwave in the context of climate change: are high-temperature extremes important for adaptation in Scotland?

Abstract: To understand whether high temperatures and temperature extremes are important for climate change adaptation in Scotland, we place the 2018 heatwave in the context of past, present, and future climate, and provide a rapid but comprehensive impact analysis. The observed hottest day (d), 5 d, and 30 d period of 2018 and the 5 d period with the warmest nights had return periods of 5-15 years for 1950-2018. The warmest night and the maximum 30 d average nighttime temperature were more unusual with return periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Climate change is unmistakeably evident in Scotland, with average temperatures between 2011–2020 being 0.9 °C warmer than the 1961–1990 average [ 54 ]. The mean temperature in Scotland is projected to continue rising with heatwaves projected to become more frequent [ 71 , 94 ], yet little is known about the impacts of high temperatures on human health in Scotland. Even though England has had a Heatwave Plan and Heat-Health Warning System in operation for almost 20 years now [ 85 ], there are still no such measures in the devolved countries of the UK, including Scotland.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is unmistakeably evident in Scotland, with average temperatures between 2011–2020 being 0.9 °C warmer than the 1961–1990 average [ 54 ]. The mean temperature in Scotland is projected to continue rising with heatwaves projected to become more frequent [ 71 , 94 ], yet little is known about the impacts of high temperatures on human health in Scotland. Even though England has had a Heatwave Plan and Heat-Health Warning System in operation for almost 20 years now [ 85 ], there are still no such measures in the devolved countries of the UK, including Scotland.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, research by King et al (2015) showed that w@h ANZ model simulations indicated a rise of hot and extreme hot days in November by at least 25 and 44%, respectively, in Brisbane. Numerous attribution studies from different parts of the world using w@h ensembles also identify the effects of anthropogenic forcing on extreme temperature events, such as Vautard et al (2020) and Undorf et al (2020) for European heat events, Philip et al (2018) in the United States and (Sparrow et al, 2018;Van Oldenborgh et al, 2018;Min et al, 2020) for different regions over Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The speed at which the overall trend declines within these regions increases until late 2017, where it continues to rapidly decrease at the same pace. This could be a result of extreme weather events during 2017 and 2018 from which the peatland has yet to recover (Fenner and Freeman, 2011;Stirling et al, 2020;Undorf et al, 2020). If the trend gradients were included in the clustering, a different region, which may not have exhibited such weather events, with different trend gradients would be classed as degraded when compared to the Flow Country.…”
Section: Discussionmentioning
confidence: 99%